The genetics of phenotypic plasticity in livestock in the era of climate change: a review. Issue 1 (14th December 2020) - Rovelli, Giacomo; Ceccobelli, Simone; Perini, Francesco; Demir, Eymen; Mastrangelo, Salvatore; Conte, Giuseppe; Abeni, Fabio; Marletta, Donata; Ciampolini, Roberta; Cassandro, Martino; Bernabucci, Umberto; Lasagna, Emiliano
Abstract: Climate change has the potential to adversely affect the health of livestock, with consequences to animal welfare, greenhouse gas emissions, productivity, human health and livelihoods. Phenotypic plasticity is the ability of a genotype to produce different phenotypes, depending on environmental, biotic or abiotic conditions; it is a factor influencing and modifying the genes of animal and plant organisms, to adaptation to climate change. Among the various climate variables, heat stress has been reported to be the most detrimental factor to the economy of the livestock industry. There are a number of candidate genes that are associated with adaptation of ruminants, monogastric and poultry to heat stress. For instance, the genes encoding leptin, thyroid hormone receptor, insulin growth factor-1, growth hormone receptor, are associated with the impacts of heat stress on the physiological pathways of domestic animals such as dairy cows, beef cattle, buffaloes, poultry, pigs and horses. This review aims to highlight genes and traits that are involved with thermo-tolerance of domestic animals to sustain production and to cope with climate change. Selection and experimental evolution approaches have shown that plasticity is a trait that can evolve when under direct selection and has a correlated response to some specific traits. Therefore, new breeding goals should be defined for the potential of livestock species to acquire plasticity for adaptation to the current climate changing conditions. Highlights: Heat stress compromises feed intake, growth, milk and meat quality and quantity, resulting in a significant financial burden to global livestock. Genetic selection and nutritional intervention are key strategies to consider in Animal Genetic Resources in hot environments. Information from gene expression or genome-wide association studies can be used to further improve the accuracy of selection.